Sunbelt blues : the failure of American housing - Ross, Andrew, 1956- (Metropolitan Books, Henry Holt and Company, 2021)
"Today, a minimum-wage earner can afford a one-bedroom apartment in only 28 out of 3,140 counties in America. The single worst place in the United States to look for affordable housing is Osceola County, Florida. Once the main approach to Disney World, where vacationers found lodging on their way to the Magic Kingdom, the fifteen-mile Route 192 corridor in Osceola has become a site of shocking contrasts. At one end, absentee investors snatch up foreclosed properties to turn into extravagant vacation homes for affluent visitors, destroying affordable housing in the process. At the other, underpaid theme park workers, displaced families, and disabled and elderly people subsisting on government checks are technically homeless, living crammed into dilapidated, roach-infested motels or even in tent camps in the woods. Through visceral, frontline reporting from the motels and encampments dotting central Florida, renowned sociologist Andrew Ross exposes the overlooked housing crisis sweeping America's suburbs and rural areas, where residents suffer ongoing trauma, poverty, and nihilism. As millions of renters face down evictions and foreclosures in the midst of the COVID-19 recession, Andrew Ross reveals how ineffective government planning, property market speculation, and poverty wages have combined to create this catastrophe. Immersive and compassionate, Sunbelt Blues finds in Osceola County a bellwether for the future of homelessness in America"--